Rancang bangun sistem pengaman kebocoran gas LPG (Liquefied Petroleum Gas) menggunakan mikrokontroler - Reza Lutfi Ismai; Jatmiko Endro Suseno; Suryono Suryono (Youngster Physics Journal, 2017)
Design of LPG gas leakage safety system using microcontroller has been made in this research. The purpose of this research is to make LPG gas sensor circuit to detect LPG gas concentration and make automation systems for LPG gas leakage protection. LPG gas leakage protection system can be applied for the use of LPG gas safely. Component to detect LPG gas concentration use sensor MQ 5 which can gives resistance as the output value which can be converted into voltage through the voltage devider circuit so that it can be read by microcontroller with ADC feature. The LPG gas concentration and the output voltage on the sensor will be displayed via LCD 16x2. When LPG gas leak occurs the LPG gas concentration detected  by sensor MQ 5 and then microcontroller will do automation such a modified regulator with a servo motor will close the LPG gas flow, buzzer will be active, the LED will be active and the relay will  exhaust LPG gas that came out due to leakage. The automation has different treatments according to the concentration range of detected LPG gas. The range of gas concentration is ppm < 500, 500 < ppm <1000 and ppm >1000. Sensor circuit can detect gas concentration up to 33000 ppm. The test result on LPG gas leak safety automation system showed that the system can work in the event of leakage of LPG gas and effective to reduce LPG gas concentration up to safe zone.Keywords: microcontroller, sensor, LPG gas, gas exhaust, automation system, exhaust system